2007
DOI: 10.1093/ajcn/85.1.193
|View full text |Cite
|
Sign up to set email alerts
|

Folate and vitamin B-12 status in relation to anemia, macrocytosis, and cognitive impairment in older Americans in the age of folic acid fortification

Abstract: In seniors with low vitamin B-12 status, high serum folate was associated with anemia and cognitive impairment. When vitamin B-12 status was normal, however, high serum folate was associated with protection against cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
391
9
16

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 528 publications
(428 citation statements)
references
References 75 publications
12
391
9
16
Order By: Relevance
“…2a) is 10-fold lower than that currently used in the above clinical trial, we anticipate that folate-labeling agents will generally be well tolerated. Third, consumption of high doses of folic acid could conceivably raise serum folate concentrations to levels that compete with folate-dye conjugates for binding to CTCs (29,30). Although no constraints were placed on vitamin utilization by the cancer patients tested in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2a) is 10-fold lower than that currently used in the above clinical trial, we anticipate that folate-labeling agents will generally be well tolerated. Third, consumption of high doses of folic acid could conceivably raise serum folate concentrations to levels that compete with folate-dye conjugates for binding to CTCs (29,30). Although no constraints were placed on vitamin utilization by the cancer patients tested in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We classified elevated MMA using 2 concentrations: .376 nmol/L (31)(32)(33)(34)(35) and .271 nmol/L (24,28,32,(36)(37)(38)(39). We also examined 4 categories of MMA based on the above cutoffs (.376 and .271 nmol/L) and .210 nmol/L (14,23,40,41). We defined elevated tHcy as a concentration .13 lmol/L (4, 16).…”
Section: Biochemical Methodsmentioning
confidence: 99%
“…The lack of effect found in this earlier trial has been partly attributed to the less-sensitive test used to assess cognitive function (mini-mental state examination) in the New Zealand trial (15) v. five separate tests of different cognitive domains used in the Dutch trial (14) . However, a recent analysis of the relationship between blood levels of folate and vitamin B 12 in older adult participants (> 60 years, n 1459) in the 1999-2002 US National Health and Nutrition Examination Survey and measures of cognitive function has found that the protective effects of folate on cognitive function are dependent on adequate vitamin B 12 status (16) . This study suggests that if vitamin B 12 status is adequate, then folic acid (even at high intake levels) seems to be protective of cognitive function (16,17) .…”
Section: Cognitive Functionmentioning
confidence: 99%